Rooting the concept of integrity in university education, an academic map to enhance integrity with public relations concepts - Jasim, Suhad Adil; Sabri, Husam M. (Al-Adab Journal, 2015)
Within the rapid communication and technological developments in the world today become for public relations specialists, researchers and international centers for studies and development in various fields and disciplines, is no longer confined to its job on the etiquette and protocol, organizing concerts and events, but beyond that to being a function contribute to the support and development of production and service institutions and even oversight institutions, need oversight institutions, in particular, has become a specialized and effective device that enable that institutions to inform what is going on around them of the developments and interactions between them and the political and social surroundings. Integrity is a human phenomenon governed by human laws and values of individuals and society, and that corresponds to this phenomenon is the goodness and the reform movement and in the contrast between these two phenomena is one of the factors which control Countries march on the ground and then control the march of human